Integrasi Kearifan Lokal Ekologis Masyarakat Baduy Pada Pembelajaran IPS Sekolah Dasar - Putri Lismawati; Encep Supriatna (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2026)
The impact of globalisation poses challenges to the preservation of local cultural identity. Education plays a vital role in preserving and instilling local culture. However, contextual learning based on local wisdom remains very limited, particularly in elementary education. This study aims to develop social studies teaching materials that integrate the ecological local wisdom of the Baduy tribe, a community that has always lived simply in harmony with nature. The Baduy community’s way of life can be used as learning material to strengthen students’ cultural awareness and environmental concern. This study employed a Research and Development approach using the ADDIE model, comprising the stages of Analyse, Design, Development, Implementation, and Evaluation. Data collection techniques included expert validation sheets, questionnaires, and pre-test and post-test instruments. The results indicated that the developed teaching materials achieved a content validity of 96%, media validity of 96%, and linguistic validity of 92%. The level of appeal reached 80%, with very positive student responses. The effectiveness test showed a significant improvement in learning outcomes with p-value of 0.001. The results demonstrate that the teaching materials are effective for use in social studies lessons and support the preservation of local culture in elementary school level.